Corporate Communication Strategy Based on Co-Creation and the Growth Zone in Optimizing Healthcare Service Performance: A Case Study at BKKP, Ministry of Transportation - Wisnu Wardana; T. Titi Widaningsih; Kholil Kholil (Eduvest - Journal of Universal Studies, 2026)
This study addresses the persistent challenges in Indonesia’s healthcare services, particularly those related to ineffective organizational communication, limited coordination, and suboptimal service performance. These issues are increasingly critical within institutions undergoing transformation, such as the Maritime Occupational Health Center (BKKP) under the Ministry of Transportation. Therefore, this study aims to develop a corporate communication strategy model based on co-creation and the growth zone to optimize healthcare service performance. This research employs a semi-quantitative approach using the MICMAC (Matrix of Cross-Impact Multiplications Applied to Classification) method. Data were collected from 85 respondents, consisting of internal staff and service users, through structured questionnaires. The analysis focuses on identifying the driving power and dependence among 18 variables categorized into co-creation, growth zone, and service performance aspects. The results indicate that communication transparency, user needs adaptation, two-way dialogue, and communicative leadership are the key variables with high driving power in shaping an effective communication strategy. In particular, user needs adaptation emerges as the most influential variable, acting as a central node in the system. Furthermore, variables such as user participation and public trust are projected to increase in importance in the future. In conclusion, integrating co-creation and growth zone approaches within corporate communication strategies significantly enhances healthcare service performance. Strengthening transparency, adaptive services, and participatory communication is essential to building a responsive, innovative, and sustainable healthcare organization.